2014
DOI: 10.1002/anie.201408693
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Located in the Dinuclear Metallo‐β‐Lactamase IMP‐1 by Pseudocontact Shifts

Abstract: Heterodinuclear metalloenzymes are an important class of metalloproteins, but determining the location of the different metal ions can be difficult. Herein we present a new NMR spectroscopy method that uses pseudocontact shifts (PCS) to achieve this without assumptions about the coordinating ligands. The approach is illustrated with the dinuclear [FeZn] complex of IMP-1, which is a prototypical metallo-β-lactamase (MβL) that confers resistance to β-lactam antibiotics. Results from single-crystal X-ray diffract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 28 publications
0
27
0
1
Order By: Relevance
“…In the case of iron, the ligand field determines whether Fe 2+ is paramagnetic or diamagnetic and whether the electron configuration in Fe 3+ ions is high-spin or low-spin [4]. Depending on the ligand field, PCSs generated by high-spin Fe 3+ can be moderately large [5] or exceedingly small [6]. The Ru 3+ ion generates sizeable PCSs [7], but most of its complexes are unstable.…”
Section: Radicals Transition Metals Lanthanidesmentioning
confidence: 99%
“…In the case of iron, the ligand field determines whether Fe 2+ is paramagnetic or diamagnetic and whether the electron configuration in Fe 3+ ions is high-spin or low-spin [4]. Depending on the ligand field, PCSs generated by high-spin Fe 3+ can be moderately large [5] or exceedingly small [6]. The Ru 3+ ion generates sizeable PCSs [7], but most of its complexes are unstable.…”
Section: Radicals Transition Metals Lanthanidesmentioning
confidence: 99%
“…For example, IMP-1 from Pseudomonas aeruginosa, a b-lactamase involved in antibiotic resistance, [66] was previously thought to exist only in ZnZn form, potentially owing to experimental artefacts; however, recent analysis revealed that a heterobinuclear Fe-Zn complex is produced in the presence of even small amounts of iron. [67] This could create an evolutionary advantage in environments with limited zinc bioavailability and varying pH ranges, as this enzyme is essential for organism fitness. Zinc is abundant in the environment, but it is restricted to very low bioavailable concentrations in the cell; [50] however, in varying pH and redox environments, redox-sensitive iron is more likely to exhibit changes in bioavailability.…”
Section: Metal Ion Promiscuity and Metalloenzyme Evolutionmentioning
confidence: 99%
“…EC number 3.5.2.6, Imipenemase (IMP) [48] Verona integron-encoded metallo-b-lactamase (VIM), [178] New Delhi metallo-b-lactamase (NDM) [179] Zn-Zn [48] Fe-Zn [67] Lactamase [180] A Enzyme Commission. different factors.…”
Section: Metal Ion Promiscuity and Metalloenzyme Evolutionmentioning
confidence: 99%
“…Jackson's research is focused on gaining a better understanding of enzyme catalysis through the use of protein crystallography, enzyme kinetics, and computational simulation, and application of this knowledge to protein engineering to produce more active and more stable catalysts. He is co‐author of a report in Angewandte Chemie on heterodinuclear metalloenzymes …”
Section: Awarded …mentioning
confidence: 99%